Eksplorasi Keterampilan Soft Skill Komunikasi Siswa (Studi Kasus Pada Siswa Desain Pemodelan Informasi Bangunan SMK Negeri 56 Jakarta) - Isya Tara Dewanto; Riyan Arthur; Eka Murtinugraha (Indo Publishing, 2026)
Communication skills are one of the important soft skills that vocational high school (SMK) students must have to support their readiness for the world of work. However, various studies show that the communication skills of SMK students are still relatively low, especially in terms of self-confidence, discussion participation, and presentation skills. This study was conducted to explore the communication skills of students majoring in Building Information Modeling Design (DPIB) at SMK Negeri 56 Jakarta and to identify the internal and external factors that influence them. This study used a qualitative approach with a case study method, involving 10th and 11th grade DPIB students as the main subjects. Data collection techniques included a attitude scale, participatory observation, and in-depth interviews with students and teachers. The data were analyzed using Miles and Huberman's interactive model through the stages of reduction, presentation, and conclusion drawing. The results of the study show differences in students' confidence in communicating at different grade levels, with grade X students having lower confidence than grade XI students. Nonverbal communication is also an aspect that is not practiced even though students are aware of its urgency. In terms of verbal communication, students are able to convey ideas and critique what is being said. Students can adjust their speaking style based on different interlocutors, for example, with teachers and friends. Then, in terms of empathy and social interaction, students are already good because they care about others in terms of interacting in the scope of vocational education. Internal factors that influence communication are intrinsic motivation and self-confidence, while external factors are learning methods that support communication habits and the role of teachers outside of school hours. The development of student communication needs to be carried out systematically through real experiences in learning, communication training, and adaptive teacher guidance. Further research is recommended to expand the scope of exploration in order to obtain a wealth of findings in the aspect of communication skills.